1999
DOI: 10.1053/hn.1999.v121.a101567
|View full text |Cite
|
Sign up to set email alerts
|

Third Place—Resident Clinical Science Award 1998: Effects ofCis‐Platinum Chemotherapy on Otoacoustic Emissions: The Development of an Objective Screening Protocol

Abstract: To develop an objective, fast, and simply performed screening protocol for cis -platinum (CP) ototoxicity, we compared the efficacy of screening with distortion-product otoacoustic emissions (DPOAEs) with the outcome of both conventional and ultra-high-frequency (UHF) audiometry. Baseline audiometric and DPOAE testing was performed in 66 patients, 33 of whom met criteria for inclusion in the final database. Comparisons were made between baseline measurements and those recorded before subsequent CP infusions. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 17 publications
5
58
1
5
Order By: Relevance
“…Currently, most ototoxicity programs monitor in the conventional frequency range only, even though numerous studies show greater sensitivity is achieved by testing frequencies above 8,000 Hz [22]. For example, one clinical study showed that if only conventional frequency testing (8,000 Hz) were used, 36 percent of initial (early detection) changes would have gone undetected [4], potentially missing the opportunity to prevent changes in the more functionally critical conventional frequencies.…”
Section: Behavioral Hearing Screening Using Comp-vamentioning
confidence: 99%
“…Currently, most ototoxicity programs monitor in the conventional frequency range only, even though numerous studies show greater sensitivity is achieved by testing frequencies above 8,000 Hz [22]. For example, one clinical study showed that if only conventional frequency testing (8,000 Hz) were used, 36 percent of initial (early detection) changes would have gone undetected [4], potentially missing the opportunity to prevent changes in the more functionally critical conventional frequencies.…”
Section: Behavioral Hearing Screening Using Comp-vamentioning
confidence: 99%
“…Evoked OAE, especially DPOAEs due to frequency specificity, were shown to be more sensitive for evaluating OHCs than were conventional audiometry, ultra high frequency audiometry, and auditory brainstem response [25]. The most important benefits of OAEs are their non-invasive capacity and objectivity to determine the early stages of sound processing and evaluate the biomechanical activity of the outer hair cells in the cochlea [26].…”
Section: Discussionmentioning
confidence: 99%
“…Sokalingam et al (2000) verificaram que o registro das emissões otoacústicas, transientes e por produto de distorção é um método sensível de avaliação do estado funcional das células ciliadas externas, e que a cobaia albina é o animal mais sensível em termos de ototoxicidade pela cisplatina, sendo que nas doses de 10 a 12 mg/kg/dia, em 3 dias já existe alteração nas emissões otoacústicas por produtos de distorção e lesão das células ciliadas externas, com depressão na amplitude dos produtos de distorção maior do que nas emissões otoacústicas transientes. 16,21,[23][24][25][26]54 Com relação à dose da cisplatina escolhida para o estudo, diversos trabalhos da literatura apontam as dosagens, via de administração e tempo de uso ideais para o estudo dos efeitos de ototoxicidade pela cisplatina. Cardinal et al (2000) mostram que nas doses de 1,5 a 2,0 mg/Kg /dia de cisplatina intraperitoneal, em cobaias albinas ocorre 60% a 65% de perda celular em 8 dias, evidenciada na espira basal da cóclea.…”
Section: Discussionunclassified
“…16,[21][22][23][24][25] Como a cisplatina atua inicialmente causando lesões nas células ciliadas externas, as emissões otoacústicas seriam um método de avaliação simples e rápido de tais danos, podendo inclusive participar na monitorização de pacientes submetidos a drogas consideradas ototóxicas. 16,[21][22][23][24][25][26] Estudos têm demonstrado um possível mecanismo antioxidante para a ototoxicidade e nefrotoxicidade geradas pela cisplatina, pois as vias de detoxicação nos dois tecidos são semelhantes. Autores mostram que os níveis de glutation e a atividade de enzimas antioxidantes como superóxido dismutase, catalase, GSH peroxidase e GSH redutase estão reduzidas nestes tecidos, levando a peroxidação lipídica, instalando assim, a toxicidade celular.…”
Section: Introductionunclassified